Alcohol-free enzyme encapsulated silica aerogel as nanobiosensor - Sani, N. S.; Lee, S. L.; Hamdan, H. (2007)
Enzyme (tyrosinase) is successfully encapsulated into nano-porous silica aerogel via an alcohol-free colloidal sol-gel route using organic-silica source. The encapsulation process was carried out at room temperature and at neutral pH to further minimize denaturation of enzymes. The leaching test showed that no significant enzymatic activity was observed in the filtrate of tyrosinase encapsulated nano-porous silica aerogel, which indicated that most of the enzyme was effectively loaded. The optimization study showed that 500 U enzyme/ g aerogel which was aged for 2 days gives the superior performance in the oxidation of catechol. The enzymatic activity of tyrosinase encapsulated nano-porous silica aerogel which was assayed through reduction of ascorbic acid using UV-Vis spectrophotometer reveals remarkable enhancement which is active at wider temperature and pH range. At pH 4 and pH 9, tyrosinase encapsulated nano-porous silica aerogel oxides catechol (phenol substitute) up to 30% after 60 minutes of reaction and it retains its enzymatic activity at 80 oC. In contrast, free tyrosinase was totally inactive at these pH values and at temperature exceeding 55 oC. This indicates that the stability of the tyrosinase towards extreme temperature as well as acidic and basic conditions is significantly improved with good reusability after the encapsulation process.